Biomechanical impacts of wearable and implantable technologies in post-surgical rehabilitation - Agrawal, Ashish; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
A revolutionary development in healthcare is the incorporation of wearable and implantable technologies into biomechanics and surgical practice. A growing number of implantable devices, including smart implants and orthopedic prosthetics, are built with sensors that allow for real-time physiological response monitoring, facilitating individualized care and recovery. Wearable technology, such as motion sensors, smart braces, and exoskeletons, also makes it possible to continuously track biomechanical functions, allowing for accurate movement analysis and the best possible recovery after surgery. These technologies work in concert to improve surgical accuracy, post-operative care, and biomechanical performance understanding, all of which lead to better long-term health outcomes and more effective rehabilitation. These systems have enormous potential to transform individualized healthcare and rehabilitation, notwithstanding obstacles concerning integration, data privacy, cost, and regulation. To bridge the gap between surgical procedures and biomechanical function and ultimately improve patient care and recovery, this abstract emphasizes the crucial intersection of wearable and implantable technology.